2013
DOI: 10.1016/j.schres.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 7Tesla imaging of the dentate granule cell layer in schizophrenia

Abstract: PURPOSE The hippocampus is central to the pathophysiology of schizophrenia. Histology shows abnormalities in the dentate granule cell layer (DGCL), but its small size (~100 micron thickness) has precluded in vivo human studies. We used ultra high field magnetic resonance imaging (MRI) to compare DGCL morphology of schizophrenic patients to matched controls’. METHOD Bilateral hippocampi of 16 schizophrenia patients (10 male) 40.7±10.6 years old (mean ±standard deviation) were imaged at 7 Tesla MRI with heavil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…Our findings are in line with a study using ultra-high-field MRI (7T) reporting a trend toward lower contrast of the dentate granule cell layer (a site of neuron proliferation and maturation) in the DG of patients with schizophrenia (52). This trend may reflect altered intracellular and extracellular water as a response to abnormal neuronal density, organization, and architecture (52). Postmortem studies have reported reduced neural stem cell proliferation in the DG of patients with schizophrenia (53) and decreased number of oligodendrocytes in CA4 (54); this could contribute to reduced myelination of the axon and impaired connectivity to CA3 (54).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with a study using ultra-high-field MRI (7T) reporting a trend toward lower contrast of the dentate granule cell layer (a site of neuron proliferation and maturation) in the DG of patients with schizophrenia (52). This trend may reflect altered intracellular and extracellular water as a response to abnormal neuronal density, organization, and architecture (52). Postmortem studies have reported reduced neural stem cell proliferation in the DG of patients with schizophrenia (53) and decreased number of oligodendrocytes in CA4 (54); this could contribute to reduced myelination of the axon and impaired connectivity to CA3 (54).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with a study using ultra-high-field MRI (7T) reporting a trend toward lower contrast of the dentate granule cell layer (a site of neuron proliferation and maturation) in the DG of patients with schizophrenia (52). This trend may reflect altered intracellular and extracellular water as a response to abnormal neuronal density, organization, and architecture (52).…”
Section: Discussionsupporting
confidence: 92%
“…A recent 7 Tesla MRI study of 16 schizophrenic patients and 15 controls, however, was able to overcome this technological limit. The investigators found that decreased contrast in the dentate granule cell layer was predictive of diagnosis [171], supporting the conclusion that granule cell abnormalities may be a feature of the disease. Finally, Dowlatshahi and colleagues (2000) found evidence for mossy fiber sprouting in tissue from 13 patients with bipolar disorder relative to 15 controls using the zinc stain for mossy fiber axons [172].…”
Section: Morphologically Abnormal Granule Cells Have Been Identifimentioning
confidence: 81%
“…Ultra-high field 7.0 Tesla (7T) MRI allows neuroimaging researchers to obtain high-resolution hippocampal microstructural images (Kerchner, 2011) and to isolate specific strata within the hippocampal subfields (Kerchner et al, 2010;Kirov et al, 2013). Hippocampal cross-sectional areas, EC thickness, and other subfield dimensions of the hippocampus can be determined by using an oblique coronal T2-weighted sequence (Kerchner et al, 2012).…”
Section: High Field Work At 7tmentioning
confidence: 99%